Toward a conceptualization of optimal self-esteem - Kernis, Michael H. (Lawrence Erlbaum Associates, Inc., 2003)
In this article, I present a theoretical perspective on the nature of "optimal" self-esteem. One of my major goals is to show that optimal and high self-esteem are different from each other. High self-esteem can be fragile or secure depending upon the extent to which it is defensive or genuine, contingent or true, unstable or stable, and discrepant or congruent with implicit (nonconscious) feelings of self-worth. Optimal self-esteem is characterized by qualities associated with genuine, true, stable, and congruent (with implicit self-esteem) high self-esteem. A second major goal is to present a conceptualization of the construct of authenticity. I propose that authenticity as an individual difference construct may be particularly important in delineating the adaptive features of optimal self-esteem. Authenticity can be characterized as the unobstructed operation of one's true, or core, self in one's daily enterprise. I argue that authenticity has 4 components: awareness, unbiased processing, action, and relational. Initial data pertaining to these components are highly encouraging. Finally, I discuss some implications of the fragile versus secure high self-esteem distinction for narcissism, defensive processing models, and cross-cultural self-esteem perspectives.